ナンキョク ドームフジ カンソクキョテン デノ シン クッサクバ ノ ケンセツ ダイ44ジ ドームフジ エットウタイ ニヨル サギョウ - 亀田, 貴雄; カメダ, タカオ; 大日方, 一夫; オビナタ, イチオ; 高橋, 暁; タカハシ, キョウ; 谷口, 健治; タニグチ, ケンジ; 杉田, 興正; スギタ, オキマサ; 藤田, 耕史; フジタ, コウジ; et al. (2005)
P(論文) 第44次南極地域観測隊ドームふじ越冬隊は2003年1月19日から2004年1月25日までドームふじ観測拠点(南緯77°19′01″,東経39°42′11″; 標高3810 m)に滞在し,雪氷・気象・宙空の観測を実施する一方,新掘削場の建設作業を実施した.この建設作業は43次隊による新掘削場の外装工事を主体した建設作業を引き継ぎ,新掘削場の内装工事を主とした.本稿では深層掘削準備作業として現地にて実施した以下の作業を記述した.ケーシングパイプ引き上げ,掘削孔拡幅,ケーシングパイプ挿入,ウインチ移設(移設用スロープの造成および10 mピット内の整備),床造成,マスト起倒用10 mピットの造成および10 mピット内の整備,ドリル作業室西側の階段造作および旧掘削場の深層ウインチ跡の床張り,机の製作,マストおよび小型門型クレーンの設置,リフター設置,ウインチ稼働テスト,チップ回収機吊り下げ用ウインチの設置,深層ウインチのケーブル巻き換え,深層ドリルの組み立ておよびマスト調整,コア貯蔵用雪洞の拡幅,コア棚の設置および一般設備工事.これらの作業に要した時間は合計で593.5日・人であり,1日平均6時間の作業時間だったので3561時・人となった.また,越冬中に実施した旧掘削場での検層準備および45次ドーム航空隊を主体とした深層掘削作業についても簡潔に記述した. Eight members of the 44th Japanese Antarctic Research Expedition (JARE-44) stayed at Dome Fuji Station (77°19′01″S, 39°42′11″E; 3810 m a.s.l.; ice thickness 3028±15 m; mean air temperature -54.4°C; lowest air temperature -79.7°C) from January 19, 2003 to January 25, 2004 for glaciological, meteorological, and upper atmospheric observations, and for construction at a new ice coring site for deep ice coring. The construction was a continuation of the activities of JARE-43; JARE-44 primarily carried out interior work at the ice coring site. The following works were carried out during the overwintering period and are described in this paper: retrieval of casing pipes from the borehole, enlargement of the borehole, insertion of casing pipes into the borehole, movement of the winch system from the old to the new ice coring sites (44.5 m apart), floor construction, construction and preparation of a 10 m depth pit for the rotating mast, construction of stairs between the old and the new ice coring sites, construction of working tables, assembling the mast and the small goliath crane, setting up a lifter, testing the winch system, setting the winch for the chip collector, cable replacement for deep ice coring, assembling of a deep ice core drill, adjustment of a rotating mast, enlargement of caves for ice core storage, and general electrical work in the new ice coring site. The total working time for the above operations was 593.5 ...